2013
DOI: 10.1530/eje-12-0191
|View full text |Cite
|
Sign up to set email alerts
|

The pubertal transition in 179 healthy Danish children: associations between pubarche, adrenarche, gonadarche, and body composition

Abstract: Background: Pubertal onset is usually defined by breast development in girls and testicular growth in boys. Pubarche is defined as the attainment of pubic hair and is considered as a sign of pubertal transition. Pubarche is preceded by a gradual increase in production of adrenal androgens, DHEA and D4-androstenedione (Adione), a process termed adrenarche. Objective: To study the natural course of pubertal transition and the associations with adrenarche, body fat, and linear growth. Design and methods: A longit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 95 publications
(58 citation statements)
references
References 38 publications
4
54
0
Order By: Relevance
“…One girl included had only three blood samples. Other aspects from this study have previously been published [10,11,12]. …”
Section: Methodsmentioning
confidence: 99%
“…One girl included had only three blood samples. Other aspects from this study have previously been published [10,11,12]. …”
Section: Methodsmentioning
confidence: 99%
“…3 Pubic hair usually follows testicular growth and breast development in boys and girls, respectively. 4 The age at pubertal onset varies between genders and individuals and is known to be influenced by many factors such as ethnicity, nutrition, genetics, and environment. [5][6][7][8] For clinical or epidemiologic studies in which exact pubertal stages are required, many aspects must be taken into consideration.…”
mentioning
confidence: 99%
“…Although biochemical adrenarche begins around the age of 6.0 years [1], Marshall and Tanner [31] reported that the mean age at development of Tanner stage II pubic hair was 11.7 years among girls in 1969. Recent studies have suggested that the mean onset age of pubarche is around 10.0 years in both Denmark and Lithuania [5,32] but 12.3 years, 1 year after breast budding, in Korea [33]. The median age at diagnosis of pubarche in NP girls was 8.9 years and only two girls were over 10 years of age (10.4 and 10.8 years) when they entered pubarche.…”
Section: Discussionmentioning
confidence: 99%